2015
DOI: 10.11610/evocs.d82
|View full text |Cite
|
Sign up to set email alerts
|

Case Study on South-Eastern Europe

Abstract: The present deliverable reports on the evolving concepts of security of Bulgaria, Serbia and Turkey. It does so in the form of national (or country) case studies which are then aggregated into a regional case study on SouthEastern Europe. The methodology used is based on the EvoCS deliverables 3.1 "Finalised analytical framework" and 4.1 "Tools for methodological support: templates, criteria and IT requirements" (see references section). Each national (and the regional) case study reports on key core values, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In the case of Bulgaria, a total of 333 pieces of information were analysed. 12 The results obtained were complemented with qualitative analysis of the security context in South-Eastern Europe by experts, who took part in a regional workshop, held in January 2015 in Sofia. 13…”
Section: On the Study's Methodologymentioning
confidence: 99%
“…In the case of Bulgaria, a total of 333 pieces of information were analysed. 12 The results obtained were complemented with qualitative analysis of the security context in South-Eastern Europe by experts, who took part in a regional workshop, held in January 2015 in Sofia. 13…”
Section: On the Study's Methodologymentioning
confidence: 99%
“…Participants in the research demonstrated a very high level of propensity to serve and that matched up well with the high level of general security awareness of the population detected in other research studies, particularly newer ones. 20 Very high propensity level (Table 1), considered in constellation with motivation structure (Table 2), can mean that participants perceive the AR as an efficient way (temporarily engagement, limited obligations) to contribute to solving the security issues in the country (belonging to the defence forces). The concept of the AR seems a promising option for successful sustainment of a relationship between the military organisation and the society: almost every citizen can try to actualise his core values related to security and to give personal contribution to the response to the security challenges, by joining the AR.…”
Section: Propensity and Motives To Serve In The Active Reservementioning
confidence: 99%